2018
DOI: 10.1186/s40794-018-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artemether-lumefantrine for the treatment of uncomplicated Plasmodium falciparum malaria in Nepal

Abstract: BackgroundThe national treatment guidelines of Nepal have adopted Artemisinin Combination Therapies (ACTs) for the treatment of uncomplicated falciparum malaria since 2004. Emergence of Artemisinin resistance in the Greater Mekong Sub-region (GMS) and beyond may become a threat for Nepal as well. The main objective of this study was to assess the therapeutic efficacy of antimalarial drug artemether-lumefantrine in uncomplicated P. falciparum infected patients at health centers/hospitals treated over the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The significant decline of confirmed malaria including P. vivax malaria during 2003 to 2012 has coincided with the scale up of free LLIN distribution policy together with the adoption of artesunate-lumefantrine as the first line of treatment for uncomplicated confirmed P. falciparum malaria [3,13]. IRS is gradually replaced by LLIN coverage in malaria-risk districts [9].…”
Section: Introductionmentioning
confidence: 99%
“…The significant decline of confirmed malaria including P. vivax malaria during 2003 to 2012 has coincided with the scale up of free LLIN distribution policy together with the adoption of artesunate-lumefantrine as the first line of treatment for uncomplicated confirmed P. falciparum malaria [3,13]. IRS is gradually replaced by LLIN coverage in malaria-risk districts [9].…”
Section: Introductionmentioning
confidence: 99%
“…With the significant reduction of malaria cases in recent years, the malaria control program in Nepal has set up the vision of “a malaria-free Nepal by 2025” and the country is currently in the pre-elimination phase (Table 4) [5, 15]. Malaria risk mapping by micro-stratification up to the VDC level is critical in order to deploy appropriate and tailored malaria control interventions to achieve the targeted goal of elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria control and elimination strategies are being accelerated in Southeast Asia and the Greater Mekong region and have mainly focused to halt the spread of artemisinin resistance using multiple control measures such as mass drug administration for malaria hotspots, strengthening village malaria workers, and deployment of LLINs with community engagement strategies wherein community members are trained and devolved with the responsibilities in the malaria risk areas which can be enhanced by malaria micro-stratification study [2432]. Even though a recent study from Nepal has not yet shown the artemisinin resistance against P. falciparum in Nepal, a continuous monitoring for resistance markers was recommended to be critical [15]. In addition, studies from Nepal have shown P. vivax as a dominating species for the last 50 years [5].…”
Section: Discussionmentioning
confidence: 99%
“…To date, hundreds of millions of malaria cases occur worldwide, most of which are caused by P. falciparum 1 . Chemical drugs have been used for the elimination of P. falciparum , such as artemisinin and its derivatives 2 , 3 , 4 , 5 . As a good antimalarial drug, chloroquine soon lost its therapeutic effect on P. falciparum after the emergence of resistant strains 6 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%